The Necessity of Studying the Islamic Legal Foundations of Caesarian Section in Medical Education with Emphasis on Health Sector Evolution - Ali Arefi-Maskoni; Mohammadreza Zangiabadi; Rahimeh Khademipour (Kerman University of Medical Sciences, 2017)
Background & Objective: The creation of culture propagation of natural childbirth and reduction of caesarian section has always been one of the objectives of the Ministry of Health and Medical Education In addition this subject is one of the 8 objectives of the countrys health system reform plan The aim of this study was the evaluation and explanation of the fundamentals caesarian section in terms of jurisprudence because medicine and jurisprudence can be related in some respects With the consideration of this connection and using Islamic resources training programs can be improved and teaching and learning output strengthened in order to better train medical students and the public on medical issues Methods: The present study was conducted through library research and by studying literature and valid first class sources of Fiqh and Hadith like Wasāil alShīʿa Man Lā Yahzar āl Faqih Mostadrakāl vasāil Qavāid āl Fiqhi and ālmizan and the religious grounds for natural childbirth Moreover books articles and dissertations in the field of medicine and the views of experts in the field were used The common points between these resources were noted in order to achieve the desired result Selection of resources was based on their accreditation  in jurisprudence and medicine Results: By studying a large number of religious Hadith and medical books related to the discussion topic it was found that natural childbirth has a scientific and rational priority over cesarean delivery except in cases of necessity However caesarian delivery is thriving today One of the most important findings of this research is that in addition to its disadvantages cesarean delivery can be indirectly effective in the reduction of population The limiting of the human race is under the "LāZarar" rules of the Islamic jurisprudence This means that harming oneself or others is not legitimate in Islam This is a good reason to study this subject in terms of Islamic jurisprudence and to guide students and researchers toward the development of medical education Conclusion: Cesarean delivery operation is one of the issues that contrary to popular imagination Islamic jurisprudence has discussed The results showed that caesarean section despite less pain than natural childbirth has no advantages over natural childbirth except in special cases and Islamic jurisprudence confirms this in numerous fatwas On the other hand cesarean section is subject to the rules of Islamic jurisprudence and according to the rule of no injury and loss in Islam (LāZarar rule) whatever causes harm to human beings is prohibited One of the major damages that cesarean delivery indirectly causes for human life is the crisis of population reduction and thus it has been forbidden according to the rule of LāZarar